Implementation of the Cambridge Curriculum-Based English Learning in Developing the Four Language Skills of High School Students: Penelitian - Khalishah Farah Rahadian; Najla Assyifa Ramadhani; Nasywa Raisa Aqilla; Maya Soraya Nasution; Tarisa Zahra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
English language skills are an important competency for high school students in the era of globalization. However, English learning still often focuses on mastering grammar and memorization, so it does not provide space for the development of language skills in a communicative and contextual manner. One approach designed to develop language skills in a balanced way is English learning based on the Cambridge Curriculum. This study aims to describe the implementation of English learning based on the Cambridge Curriculum in developing four language skills, namely listening, speaking, reading, and writing, in students of Jabal Rahmah Mulia Boarding School. This research uses a qualitative approach with a descriptive design. The research subjects consisted of 21 grade XII students and 5 English teachers. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion drawn, while data validity is ensured through triangulation of sources and techniques. The results of the study show that the implementation of the Cambridge Curriculum is carried out systematically and integrated with the Independent Curriculum and the Tahfidz Al-Qur'an program. Learning is designed to develop four language skills in a balanced manner through a communicative approach, familiarization of English in the dormitory environment (English Area), interaction with native speakers, and international standard evaluation. This implementation is supported by a conducive learning environment, the availability of facilities and infrastructure, as well as academic achievement targets in the form of Cambridge certification and IELTS scores. Thus, English learning based on the Cambridge Curriculum plays an effective role in improving students' English language competencies while supporting students' academic readiness and character in the boarding school environment.